Frequency dependence on space-time for elastomagnetic propagation in dispersive medium - Ciarkowski, A. (Archives of Mechanics, 1999)
Propagation of an electromagnetic high-frequency modulated signal in a lossy dispersive Lorentz medium is reconsidered. A new approximate solution is found to the equation relating complex frequency of the propagating signal and the space-time point. This solution is compared numerically with the solution to the saddle point equation in the special case of the Brillouin medium parameters.